Antifungal activity of essential oils against itraconazoleresistant pathogenic Candida isolated from vulvovaginal candidiasis - Ali AL-Janabi (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Fungal infection by species of pathogenic Candida withantifungal resistance is currently a serious problem. Treatment with new medications isbecoming more challenging to manage this type of infection. The present study aimed to investigate the antifungal effect of essential oils (EOs) against itraconazole-resistantspecies of pathogenic Candida.Materials and Methods: Seven essential oils were tested on 15 clinical isolates ofitraconazole-resistant Candida from patients with vulvovaginal candidiasis. Theantifungal action of selected EOs was evaluated using the disc diffusion method with the determination of the minimum inhibitory concentration (MIC) of effective EOs.Results: Radish EO was the most effective type against all Candida isolates with MICsbetween 3.125% and 6.25% (v/v) .It also had a stronger effect than itraconazole. Sixother EOs showed antifungal effects at varying concentrations and were dependent upon the type of isolate. Low concentrations of these six EOs were more effective against many isolates than their high concentrations. Moreover, camphor and linseed EOs were less effective on isolates.Conclusion: Radish EO has a strong antifungal activity against itraconazole-resistancespecies of Candida, even more than itraconazole. The antifungal action of some EOs can be increased through the use of low concentrations.